The Subtle Marks of the Damage Caused by Colonization in Sub-Saharan Africa: Case Study of Cameroon - (:unkn) unknown (My University, 2023)
The aim of this study was to identify the consequences of colonization in the daily lives of African peoples in sub-Saharan Africa. For this, many actions have been carried out. From the 4,500 men interviewed, 3,010 would choose a light-skinned wife and 1,000 a dark-skinned wife; 490 are not influenced by skin complexion. From the 4,500 women interviewed, 2004 would choose a light-skinned man and 644 a dark-skinned man. 1852 are not influenced by skin complexion. From the 4500 women, 3800 would like to have a fair complexion and 500 a dark complexion; 200 are indifferent. From the 500 children interviewed, 379 liked fair complexion, against 121 for dark complexion. Many people worship the white man. We find the signs of this on a daily basis: The best places are always reserved for the white man on all occasions; the way peoples interprate a successful action or a purchasing power; The efforts made to speak like white men; The rejection of one’s language and one’s tribal name in favor of those imported; The pronounced taste for imported clothing products. Concerning the musical and choreographic preferences, we can classify the young peoples interviewed as follows: 50.2% strictly in favor of imported dances and music styles; 26.2% love both imported and Cameroonian music and dance styles; 23.5% in favor of strictly Cameroonian dances and music styles. In the same vein, we have for hairdressing: 28.33% for grafting; 21.89% for the use of wigs; 15.82% for Afro-style. The choirs which practice the folk style are always lowered in front of those which practice the baroque style. In view of this dark picture, we can notice in detail that there is a segment of the African population south of the Sahara, even if it is a minority, which lives its Africanness with pride. It therefore constitutes the hope for the rebirth of African culture.
Keywords: African Research